141k views
2 votes
Given f(x) = 3x -1 & g(x)= -x + 6, find f(-2) + g(5)​

User Phse
by
5.7k points

1 Answer

5 votes

Answer:

When added together, the sum of the given functions have a value of -6.

Explanation:

When we see f(-2), it means that our value of x for the f(x) function is -2. When we see g(5), it means that our value of x for the g(x) function is 5. So, let's use this information and plug it into our equation.

f(-2) + f(5) = (3(-2) - 1) + (-(5) + 6)

Multiply 3 by -2 and distribute the negative to 5.

f(-2) + f(5) = (-6 - 1) + (-5 + 6)

Subtract 1 from -6 and add 6 to -5.

f(-2) + f(5) = (-7) + (1)

Add 1 to -7.

f(-2) + f(5) = -6

So, when added, the sum of the functions is -6.

User Nasaralla
by
5.5k points